STRATEGY FOR OPTIMIZING INTERNAL AUDITING FINANCIAL CONTROL OF THE COMPANY DURING THE ECONOMIC CRISIS - A. V. Gladysheva; I. N. Makhonina; I. F. Chepurova (Вестник университета)
The article considers the process of strategic transformation of the company’s internal audit as an effective form of the financial control system, which is a structurally branched set of interrelated links. The paper analyses various aspects of organization management in the context of global crisis phenomena in socio-economic and other spheres. The author proposes a set of measures to adapt the company to work during the Covid-19 pandemic impact on the economy. The study clarifies fundamentally new requirements to the content of the internal audit service specialists` functionality and the nature of their interaction with top management representatives. The paper outlines the prospects of professional development of the auditor in modern conditions.